2016
DOI: 10.1186/s40359-016-0139-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline in Twin Families (VIPP-Twins): Study protocol for a randomized controlled trial

Abstract: BackgroundIntervention programs with the aim of enhancing parenting quality have been found to be differentially effective in decreasing negative child outcomes such as externalizing behavioral problems, resulting in modest overall effect sizes. Here we present the protocol for a randomized controlled trial to examine the efficacy of the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline for Twin Families (VIPP-Twins) on parenting quality and children’s behavioral control and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 44 publications
0
63
0
Order By: Relevance
“…However, test–retest reliability studies on task‐based fMRI in developmental samples have shown higher interclass correlation coefficients (ICCs) for lateral PFC regions than for subcortical regions (Peters, Van Duijvenvoorde, Koolschijn, & Crone, ; van den Bulk et al, ), indicating that the DLPFC might indeed reflect trait‐like genetic influences. An important next step would be to reveal which environmental and genetic factors play a role in explaining the variance in brain activation and aggression following social evaluation, and test whether specific environmental influences (e.g., supportive parenting) might moderate the influence of specific genetic factors (for example, see the study protocol of Euser et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, test–retest reliability studies on task‐based fMRI in developmental samples have shown higher interclass correlation coefficients (ICCs) for lateral PFC regions than for subcortical regions (Peters, Van Duijvenvoorde, Koolschijn, & Crone, ; van den Bulk et al, ), indicating that the DLPFC might indeed reflect trait‐like genetic influences. An important next step would be to reveal which environmental and genetic factors play a role in explaining the variance in brain activation and aggression following social evaluation, and test whether specific environmental influences (e.g., supportive parenting) might moderate the influence of specific genetic factors (for example, see the study protocol of Euser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…indicating that the DLPFC might indeed reflect trait-like genetic influences. An important next step would be to reveal which environmental and genetic factors play a role in explaining the variance in brain activation and aggression following social evaluation, and test whether specific environmental influences (e.g., supportive parenting) might moderate the influence of specific genetic factors (for example, see the study protocol of Euser et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is part of the Leiden Consortium on Individual Development project (L-CID), a longitudinal intervention study in which families with same-sex twins participate (Euser et al, 2016). Within the L-CID study, 40% of the sample was randomly assigned to the VIPP-SD and 60% to the control condition by using a computer-generated blocked randomization sequence with a ratio of 2:3 stratified on gender of the parents.…”
Section: Participantsmentioning
confidence: 99%
“…Participants took part in a larger longitudinal intervention study of the Leiden Consortium on Individual Development (L-CID; Euser et al, 2016). We recruited families with same-sex twins born between 2010 and 2013 via municipal authorities in the western part of The Netherlands.…”
Section: Participantsmentioning
confidence: 99%